Penggunaan Media Sosial oleh Digital Native - Supratman, Lucy Pujasari (Jurnal ILMU KOMUNIKASI, 2018)
The lack of digital media literacy education shall become requirement to the rises of horribly phenomenon in Indonesia. The purpose of this study is to create the awareness on using social media smartly.Â  I used qualitative method that had been taken through purposive sampling. Since the Collaborative Learning Model of Digital Media Literacy was applied, students mindset about Digital Media Literacy meaning had shifted into the wiser social media users.